2018
DOI: 10.1186/s12889-018-5172-8
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and risk of respiratory tract infections: results of an infection-diary based cohort study

Abstract: BackgroundRespiratory tract infections (RTIs) are a major morbidity factor contributing largely to health care costs and individual quality of life. The aim of the study was to test whether obesity (BMI ≥ 30 kg/m2) is one of the risk factors underlying frequent RTIs in the German adult population.MethodsWe recruited 1455 individuals between 18 to 70 years from a cross-sectional survey on airway infections in Germany and invited them to self-report in diaries incident RTIs experienced during three consecutive w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 35 publications
4
50
0
2
Order By: Relevance
“…Excess body weight has been linked to immunological imbalances that can manifest as increased susceptibility to infections including URTIs 52 ; such infections can impart a considerable socioeconomic burden 53 . Probiotics have been found to have a preventative effect on the incidence/severity of URTI 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Excess body weight has been linked to immunological imbalances that can manifest as increased susceptibility to infections including URTIs 52 ; such infections can impart a considerable socioeconomic burden 53 . Probiotics have been found to have a preventative effect on the incidence/severity of URTI 54 .…”
Section: Discussionmentioning
confidence: 99%
“…The evidence has been confirmed elsewhere ( 38 , 39 ). Accordingly, Maccioni et al ( 40 ) recruited 1455 individuals aged 18–70 in a cross-sectional study on airway infection in Germany. The study reported that obese persons have a consistently higher frequency of upper and lower respiratory tract infections (RTIs).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity contributes to worse disease outcome in viral infections. Obesity has been found to be associated with increased frequency of both upper respiratory tract infections (adjusted OR 1.55) and lower respiratory tract infections (adjusted OR 2.02) 45 . In a mouse model, when diet‐induced obese (DIO) mice and lean mice were infected with mouse‐adapted influenza virus, the DIO mice had greater mortality than the lean mice (42% vs 5.5%) 46 .…”
Section: Obesity and Respiratory Virusesmentioning
confidence: 99%